Acute effects of a novel treadmill device on gait and postural control in patients with Parkinson’s disease - Klamroth, Sarah; Steib, Simon; Gaßner, Heiko; Winkler, Jürgen; Eskofier, Björn; Klucken, Jochen; Pfeifer, Klaus (ISPGR World Congress, 2015)

Acute effects of a novel treadmill device on gait and postural control in persons with Parkinson’s disease - Bernhardt, Sarah; Devan, Surendar; Novokreshchenova, Lyusyena; Steib, Simon; Pfeifer, Klaus (ECSS 2014 – Book of Abstracts, 2014)

Acute effects of perturbation treadmill training on gait and postural control in patients with Parkinson’s disease - Steib, Simon; Klamroth, Sarah; Gaßner, Heiko; Goßler, Julia; Eskofier, Björn; Winkler, Jürgen; Klucken, Jochen; Pfeifer, Klaus (Crossing borders through sport science. ECSS - Book of Abstracts, 2016)

Acute Neuromuscular Adaptations in the Postural Control of Patients with Parkinson’s disease after Perturbed Walking - Pasluosta, Cristian Federico; Steib, Simon; Klamroth, Sarah; Gaßner, Heiko; Goßler, Julia; Hannink, Julius; Von Tscharner, Vinzenz; Pfeifer, Klaus; Winkler, Jürgen; Klucken, Jochen; Eskofier, Björn (Frontiers in Aging Neuroscience, 2017)

Akute Anpassungen des Gangbildes und Gleichgewichts an ein sensomotorisches Laufbandtraining bei Patienten mit Morbus Parkinson - Klamroth, Sarah; Steib, Simon; Gaßner, Heiko; Winkler, Jürgen; Eskofier, Björn; Klucken, Jochen; Pfeifer, Klaus (Moving Minds - Crossing Boundaries in Sport Science, 2015)

An overview of physical activity referral schemes worldwide and their key interventional components - Mino, Eriselda; Hanson, Coral; Geidl, Wolfgang; Naber, Inga; Weißenfels, Anja; Mchale, Sheona; Klamroth, Sarah; Gelius, Peter; Abu-Omar, Karim; Pfeifer, Klaus (European Society of Cardiology (ESC), 2022)

Are physical activity referral scheme components associated with increased physical activity, scheme uptake, and adherence rate? A meta-analysis and meta-regression - Mino, Eriselda; Pfeifer, Klaus; Hanson, Coral L.; Schuler, Michael; Brandmeier, Anna; Klamroth, Sarah; Naber, Inga; Weißenfels, Anja; McHale, Sheona; Abu-Omar, Karim; Gelius, Peter; Whiting, Stephen; et al. (International Journal of Behavioral Nutrition and Physical Activity, 2024)
Background: Physical activity referral schemes (PARS) are composed of various components, such as a written prescription or a person-centered approach. The role of these components in their effectiveness is yet to be understood. Therefore, we aimed to explore the relationships between PARS components and physical activity, scheme uptake, and adherence rate; and to estimate the effect of PARS. Methods: We searched Scopus, PubMed, Web of Science, CINAHL, ScienceDirect, SpringerLink, HTA, Wiley Online Library, SAGE Journals, Taylor & Francis, Google Scholar, OpenGrey, and CORE. Eligible studies were published between 1990 and November 2023 in English or German, investigated PARS with participants aged ≥ 16 years, and reported physical activity, scheme uptake, or scheme adherence. Separate random-effects meta-analysis by comparison group were conducted for physical activity. Scheme uptake and adherence rates were pooled using proportional meta-analysis. The components were analyzed via univariate meta-regression. We rated the risk of bias using RoB2 and ROBINS-I, and the certainty of evidence using GRADE. Results: Fifty-two studies were included. PARS were more effective in increasing physical activity than usual care (k = 11, n = 5046, Hedges’ g = 0.18, 95%CI 0.12 to 0.25; high certainty of evidence). When PARS were compared with physical activity advice or enhanced scheme versions, the pooled Hedges’ g values for physical activity were -0.06 (k = 5, n = 1082, 95%CI -0.21 to 0.10; low certainty of evidence), and 0.07 (k = 9, n = 2647, 95%CI -0.03 to 0.18; low certainty of evidence) respectively. Scheme uptake was 87% (95%CI 77% to 94%, k = 14, n = 5000) across experimental studies and 68% (95%CI 51% to 83%, k = 14, n = 25,048) across non-experimental studies. Pooled scheme adherence was 68% (95%CI 55% to 80%, k = 16, n = 3939) and 53% (95%CI 42% to 63%, k = 18, n = 14,605). The meta-regression did not detect any significant relationships between components and physical activity or scheme uptake. A person-centered approach, screening, and brief advice were positively associated with scheme adherence, while physical activity sessions were negatively associated. Conclusion: PARS are more effective in increasing physical activity than usual care only. We did not identify any components as significant predictors of physical activity and scheme uptake. Four components predicted scheme adherence, indicating that the component-effectiveness relationship warrants further research.
CRIS-Team Scopus Importer:2024-08-09
Keywords: Exercise prescription; Exercise referral scheme; Physical activity; Physical activity prescription; Physical activity referral scheme; Referral and consultation

A systematic review and narrative synthesis of physical activity referral schemes’ components - Mino, Eriselda; Hanson, Coral L.; Naber, Inga; Weißenfels, Anja; Mchale, Sheona; Saftig, Jane; Klamroth, Sarah; Gelius, Peter; Abu-Omar, Karim; Whiting, Stephen; Wickramasinghe, Kremlin; Galea, Gauden; et al. (International Journal of Behavioral Nutrition and Physical Activity, 2023)
Background Physical activity referral schemes (PARS) are complex multicomponent interventions that represent a promising healthcare-based concept for physical activity (PA) promotion. This systematic review and narrative synthesis aimed to identify the constitutive components of PARS and provide an overview of their effectiveness. Methods Following a published protocol, we conducted a systematic search of PubMed, Scopus, Web of Science, CINAHL, ScienceDirect, SpringerLink, HTA, Wiley Online Library, SAGE Journals, Taylor & Francis, Google Scholar, OpenGrey, and CORE from 1990 to January 2023. We included experimental, quasi-experimental, and observational studies that targeted adults participating in PARS and reported PA outcomes, scheme uptake, or adherence rates. We performed an intervention components analysis using the PARS taxonomy to identify scheme components and extracted data related to uptake, adherence, and PA behavior change. We combined these to provide a narrative summary of PARS effectiveness. Results We included 57 studies reporting on 36 PARS models from twelve countries. We identified 19 PARS components: a patient-centered approach, individualized content, behavior change theory and techniques, screening, brief advice, written materials, a written prescription, referral, baseline and exit consultation, counselling support session(s), PA sessions, education session(s), action for non-attendance, structured follow-up, a PA network, feedback for the referrer, and exit strategies/routes. The PARS models contained a mean of 7 ± 2.9 components (range = 2–13). Forty-five studies reported PA outcome data, 28 reported uptake, and 34 reported adherence rates. Of these, approximately two-thirds of studies reported a positive effect on participant PA levels, with a wide range of uptake (5.7–100.0%) and adherence rates (8.5–95.0%). Conclusions Physical activity referral scheme components are an important source of complexity. Despite the heterogeneous nature of scheme designs, our synthesis was able to identify 19 components. Further research is required to determine the influence of these components on PARS uptake, adherence, and PA behavior change. To facilitate this, researchers and scheme providers must report PARS designs in more detail. Process evaluations are also needed to examine implementation and increase our understanding of what components lead to which outcomes. This will facilitate future comparisons between PARS and enable the development of models to maximize impact.
Keywords: physical activity; physical activity referral scheme; physical activity on prescription

Aufbau eines Interventionskonzeptes zur Förderung der bewegungsbezogenen Gesundheitskompetenz in der Gesundheitsversorgung - Naber, Inga; Klamroth, Sarah; Weißenfels, Anja; Geidl, Wolfgang; Mino, Eriselda; Gelius, Peter; Abu-Omar, Karim; Pfeifer, Klaus (Jahrestagung dvs-Kommission Gesundheit, 2022)
Einleitung Für die Bewegungsförderung von Menschen mit nichtübertragbaren Erkrankungen (non-communicable diseases – NCD) kann die ärztlich-initiierte Verordnung von körperlicher Ak-tivität als wirksame Methode eingesetzt werden. Wird dabei zudem die bewegungsbezo-gene Gesundheitskompetenz (BGK) gefördert, so sind positive Effekte auf das Bewegungs-verhalten zu erwarten. Entsprechend wurde im Rahmen des Forschungsprojektes Bewegt-Versorgt eine ärztlich-initiierte Bewegungsversorgungskette entwickelt, dessen Kernkompo-nente eine BGK-basierte individuelle Bewegungsförderung (IBF) zur Umsetzung in der Ge-sundheitsversorgung darstellt. Die Entwicklung und Gestaltung der IBF soll im vorliegenden Beitrag vorgestellt werden. Methode Die IBF wurde in enger Zusammenarbeit mit Projektpartnerinnen und -partnern aus dem Bereich der Bewegungsförderung entwickelt. Hierfür wurden a) evidenzbasierte Methoden und Inhalte aus anderen Studien sowie theoretische Grundgedanken zur Bewegungsförde-rung berücksichtigt. Dabei erfolgte eine Orientierung am BGK-Modell sowie an Rahmenkon-zepten zur Entwicklung von verhaltensbezogenen Interventionsprogrammen (u.a. Interven-tion Mapping, Techniken zur Verhaltensänderung). Die selektierten Inhalte und Methoden wurden b) von Expertinnen und Experten aus Forschung und Praxis besprochen und adap-tiert. Anschließend wurden c) die festgelegten inhaltlichen und methodischen Elemente in ein modulares Konzept transferiert und durch Arbeitsmaterialien ergänzt. Ergebnisse Das modulare Interventionskonzept der IBF integriert BGK-spezifische Inhalte und umfasst eine 1:1 Betreuung durch geschultes Bewegungsfachpersonal über einen Zeitraum von 24 Wochen (6 Einheiten à 60 Minuten, 3 Assessments). Basierend auf den jeweiligen Voraus-setzungen, Bedürfnissen und Präferenzen der Teilnehmenden werden verschiedene Bewe-gungsformen ausprobiert und ein individuell angepasster Bewegungsplan entwickelt. Wäh-rend der IBF wird durch die gezielte Unterstützung bei der Handlungsplanung und bei der Kontaktaufnahme mit Bewegungsanbietern die Überführung in eigenständige körperliche Aktivität angestrebt. Diskussion Im Rahmen eines Modellvorhabens nach §§ 63 Abs. 2, 64 SGB V wird die IBF derzeit in der Gesundheitsversorgung erprobt. Hier wird sich zeigen, inwieweit das Interventionskonzept wie geplant umgesetzt werden kann und wie wirksam es in Hinblick auf die Steigerung der körperlichen Aktivität und der BGK ist.<br
Keywords: körperliche Aktivität; bewegungsbezogene Gesundheitskompetenz

BewegtVersorgt: co-development of a physical activity referral scheme for use in the German healthcare system - Mino, Eriselda; Naber, Inga; Weißenfels, Anja; Klamroth, Sarah; Geidl, Wolfgang; Gelius, Peter; Abu-Omar, Karim; Pfeifer, Klaus (20. Deutscher Kongress für Versorgungsforschung, 2021)
Background and status of (inter)national research: Physical activity referral schemes (PARSs) are a well-known method of promoting physical activity among the inactive primary care population with or at risk of developing non-communicable diseases. Despite significant expansion throughout Europe, a national scheme has not yet been established in Germany. Thus, similar efforts were initiated in June 2019 through the BewegtVersorgt project. Objectives: To design a PARS model with the premise of future integration into the German healthcare system. Methods: A co-production approach, including scenario thinking elements and cooperative planning, was utilized to develop the PARS. The research team worked closely together with twelve organizations from various sectors - health insurances, physicians, physiotherapists, sports, and patient organizations. Twelve bilateral meetings were conducted from June to September 2019, with the stakeholders exploring their PARS vision. These were followed by three half-day co-production meetings held in presence, which took place from October 2019 until January 2020. Successive negotiation meetings were organized to refine and finalize the co-developed work. The final PARS was held forward for approval by the end of 2020 in an online stakeholder meeting. Results: The co-produced PARS starts with the primary care physician, as the gatekeeper in the German healthcare system, who offers 10 min physical activity advice to the patients who would benefit from physical activity participation. Afterward, the patients are referred to an exercise professional through a referral form. The exercise professional delivers the remaining central components of the intervention - initial assessment, six 1-hour individual physical activity counseling sessions spread throughout 12 weeks, final assessment, a progress report to the general practitioner, and one follow-up visit at six months. The intervention uses a patient-centered approach and motivational interviewing. The end goal is an adaptation of an active lifestyle and transfers to local physical activity opportunities. Discussion: This PARS was comprehensively designed based on coordinated efforts from various areas of expertise. The involvement of key stakeholders ensured that the final PARS incorporates scheme providers, funders, and service-users perspectives. The combination of international scientific evidence and practical knowledge ensures higher feasibility and acceptability of the intervention. Practical implications: If proved efficacious, the successful integration of the PARS in routine practice will likely benefit the chronically ill population. Consequently, this would translate into favorable economic implications. Further, this PARS has implications for health and exercise professionals who contemplate integrating physical activity promotion and behavior change aspects into their care standards. Appeal to practice (science and/or care) in one sentence: This health insurance covered PARS presents an opportunity for inter-sectoral collaboration between sport/physical activity and healthcare professionals.

BewegtVersorgt: Entwicklung neuer Versorgungsstrukturen zur Bewegungsförderung mit Hilfe eines Co-Production Ansatzes - Klamroth, Sarah; Weißenfels, Anja; Mino, Eriselda; Naber, Inga; Geidl, Wolfgang; Gelius, Peter; Abu-Omar, Karim; Pfeifer, Klaus (25. Sportwissenschaftlicher Hochschultag der Deutschen Vereinigung für Sportwissenschaft (dvs), 2022)

BewegtVersorgt: Projektvorstellung und erste Erkenntnisse - Weißenfels, Anja; Klamroth, Sarah; Naber, Inga; Mino, Eriselda; Geidl, Wolfgang; Gelius, Peter; Abu-Omar, Karim; Pfeifer, Klaus (Sports, Medicine and Health Summit 2023, 2023)

Bewegungsförderung im deutschen Gesundheitssystem – Vorstellung einer pragmatischen Studie im Cluster-Design - Weißenfels, Anja; Klamroth, Sarah; Naber, Inga; Mino, Eriselda; Geidl, Wolfgang; Gelius, Peter; Abu-Omar, Karim; Pfeifer, Klaus (25. dvs-Hochschultag "Sport,Mehr & Meer - Sportwissenschaft in gesellschaftlicher Verantwortung", 2022)
Einleitung Die zunehmende Inaktivität in der Bevölkerung macht es erforderlich, dass gezielte Maßnahmen zur Bewegungsförderung zum festen Bestanteil der Gesundheitsversorgung werden, wie es international bereits etabliert ist. Mit der Implementierung solcher bewegungsbezogenen Versorgungsstrukturen im deutschen Gesundheitssystem setzt sich das Projekt BewegtVersorgt auseinander. Hierbei werden über einen ‚co-production‘ Ansatz gemeinsam mit Akteuren des Gesundheitssystems Versorgungsketten zur verhaltensbezogenen Bewegungsförderung für Menschen mit nichtübertragbaren chronischen Erkrankungen entwickelt hat, die anschließend direkt in der Regelversorgung implementiert, erprobt und evaluiert werden sollen. Die Kernkomponente ist eine enge Zusammenarbeit zwischen ärztlichem Fachpersonal und Bewegungsexperten. Die Ziele der pragmatischen Studie beziehen einerseits die Überprüfung der Wirksamkeit der entwickelten Versorgungskette (u. a. Veränderung der körperlichen Aktivität, bewegungsbezogenen Gesundheitskompetenzen, Lebensqualität) und andererseits auch deren Implementierung in die Routineversorgung ein. Methodik Die pragmatische Studie ist als cluster-randomisierte kontrollierte Studie (cRCT) geplant und umfasst zwei Interventionsgruppen. Während eine Gruppe eine Kombination aus ärztlicher Kurzberatung und individueller Bewegungsförderung durch geschultes Bewegungsfachpersonal erhält (physical activity referral scheme – PARS), bekommt die Vergleichsgruppe eine ärztliche Kurzberatung und Informationsmaterial zur eigenständigen körperlichen Aktivität (physical activity advice – PAA). Geplant ist ein cRCT, bei dem 24 ärztliche Praxen randomisiert den beiden Interventionsarmen zugeordnet werden und insgesamt 552 Teilnehmende rekrutieren, beraten und entsprechend ihrer Gruppenzugehörigkeit weiterleiten. Zur Beantwortung der Fragestellungen bedient man sich einem Hybrid II – Design, wobei die Wirksamkeit der Intervention verstärkt über standardisierte Fragebögen evaluiert wird, während der Implementierungserfolg u. a. mittels qualitativer Interviews der ausführenden Akteure untersucht werden soll. Diskussion Durch die gemeinsame Entwicklung mit Akteuren des Gesundheitssystems erhofft man sich eine größtmögliche Akzeptanz der neuen Versorgungsstruktur und eine nachhaltige Verankerung in der Gesundheitsversorgung. So wird die Studie durch die Zusammenarbeit mit Kostenträgern als Modellvorhaben nach §§ 63 Abs. 2, 64 SGB V implementiert, die Akteure erhalten eine Leistungsvergütung und bereits bestehende Abrechnungswege sowie Strukturen innerhalb der ärztlichen wie auch therapeutischen Einrichtungen werden integriert. <br
Keywords: Verhaltensbezogene Bewegungsförderung; Gesundheitsversorgung

Bewegungsversorgung im deutschen Gesundheitssystem: gesundheitspolitische Relevanz und notwendige Rahmenbedingungen – ein Positionspapier der AG Bewegungsbezogene Versorgungsforschung des DNVF - Schaller, Andrea; Thiel, Christian; Peters, Stefan; Geidl, Wolfgang; Klamroth, Sarah; Lange, Martin; Kastaun, Sabrina; Krupp, Sonja; Spaderna, Heike; Eckert, Katharina; Grafe, Marion; Voelcker-Rehage, Claudia; et al. (Gesundheitswesen, 2024)
Based on the relevance of an established and broad foundation of physical activity in healthcare, this position paper of the DNVF working group Physical Activity-Related Health Services research presents current conceptual approaches to physical activity-related health services in Germany and highlights the need for interprofessional and interdisciplinary approaches. Three central positions are outlined and elaborated in order to integrate the evidence on health benefits of physical activity and exercise more strongly into healthcare and to show that, against the background of the challenges in the German healthcare system, physical activity-related health services can make a cost-effective and high-quality contribution to improve healthcare. These three positions include 1) the integration of all professional groups involved in healthcare into physical activity-related health services, 2) the greater integration of physical activity professions and physical activity interventions into all healthcare contexts and 3) the systematic consideration of physical activity- and exercise-related expertise in clinical guidelines.
CRIS-Team Scopus Importer:2024-11-22
Keywords: Health services research; Healthcare system; Interdisciplinarity; Interprofessionality; Physical Activity-Related Health Services

Bewertung bestehender Versorgungsketten zur Bewegungsförderung im deutschen Gesundheitssystem - Naber, Inga; Weißenfels, Anja; Geidl, Wolfgang; Mino, Eriselda; Klamroth, Sarah; Gelius, Peter; Abu-Omar, Karim; Pfeifer, Klaus (20. Deutscher Kongress für Versorgungsforschung, 2021)
Hintergrund und Stand (inter)nationaler Forschung: Im internationalen Kontext sind Bewegungsversorgungsketten (BVKs) bereits erfolgreich in die Regelversorgung eingebettet (z.B. Schweden). Dies befürworten auch die nationalen Empfehlungen für Bewegung und Bewegungsförderung, um nachhaltig die steigende Inzidenz von körperlicher Inaktivität bei Menschen mit nichtübertragbaren Erkrankungen oder manifesten Risikofaktoren für diese zu reduzieren. Im deutschen Gesundheitssystem bestehen bereits BVKs, deren spezifischer Bezug zur verhaltensbezogenen Bewegungsförderung jedoch bisher noch nicht erforscht worden ist. Zielsetzung: Daher sollen die identifizierten ärztlich initiierten BVKs für Rehabilitationssport (RS), Funktionstraining (FT), Physiotherapie (PT) und Präventionsprogramme (PP) hinsichtlich einer nachhaltigen Bewegungsförderung analysiert werden. Methode: Auf Grundlage der Qualitätskriterien zur Konzipierung, Implementierung und Evaluation von Interventionen zur Bewegungsförderung wurden öffentliche Dokumente systematisch geprüft. Zur Bewertung der BVKs mussten die Qualitätskriterien thematisch angepasst und über eine Expertenbefragung validiert werden. Die Bewertung der identifizierten BVKs erfolgte über zwei unabhängige Wissenschaftler („0“ nicht bewertbar bis „3“ trifft voll zu). Im Fokus der Analyse standen die Interrater Reliabilität (Cohens Kappa k) sowie die Häufigkeiten der Bewertungsskala. Ergebnisse: Ausgehend von der Analyse zweier unabhängiger Wissenschaftler lag die Interrater Reliabilität k bei .89. Der Bereich Nachhaltigkeit wurde bei allen BVKs als sehr gut bewertet. In Kategorien wie Multidimensionalität, Ziele und Zielverhalten, Befähigung sowie Qualität der Evaluation wurden Komponenten der Bewegungsförderung dagegen nicht ausführlich beschrieben oder nicht erwähnt. Diskussion: Das Bewertungstool ließ eine Analyse der BVKs hinsichtlich bewegungsförderlicher Komponenten zu, welches zeigt, dass die analysierten Interventionen die Qualitätskriterien bereits in vielen Kategorien erfüllen. Herauszustellen ist jedoch, dass wesentliche Aspekte, insbesondere bei RS, FT und PT, auf Grund fehlender Informationen nicht bewertbar sind. Eine Anpassung der fehlenden oder ungenügenden Informationen würde das Gesamtbild komplementieren und nach erfolgreichem Transfer in die Praxis möglicherweise die Qualität der Versorgungswege steigern. Praktische Implikationen: Um körperliche Aktivität nachhaltig in der Gesellschaft zu verankern, scheint eine verhaltensbezogene Bewegungsförderung, die durch Ärzt*innen initiiert wird, großes Potenzial zu haben. Zur Umsetzung bedarf es jedoch Anpassungen in den bestehenden gesetzlichen Rahmen- sowie Schulungskonzepten oder einer Entwicklung neuer Ansätze mit verhaltensbezogenem Fokus. Appell für die Praxis: Die Entwicklung einer spezifischen Versorgungskette zur verhaltensbezogenen Bewegungsförderung sollte auf Basis aller analysierten Stärken und Schwächen bereits bestehender BVKs vorangetrieben werden.

Co-producing a physical activity referral scheme for the German healthcare system: A qualitative analysis of stakeholder experiences - Klamroth, Sarah; Mino, Eriselda; Naber, Inga; Weißenfels, Anja; Geidl, Wolfgang; Gelius, Peter; Abu-Omar, Karim; Pfeifer, Klaus (15th conference of HEPA Europe "Optimising health enhancing physical activity: the importance of inclusion", 2024)

Coproducing a physical activity referral scheme in Germany: A qualitative analysis of stakeholder experiences - Klamroth, Sarah; Mino, Eriselda; Naber, Inga; Weißenfels, Anja; Geidl, Wolfgang; Gelius, Peter; Abu-Omar, Karim; Pfeifer, Klaus (BMJ Open, 2024)
Objectives This study evaluated stakeholders' experiences of participating in a coproduction process to develop a physical activity referral scheme (PARS) in the German healthcare system. The focus was on examining facilitators and challenges, along with gathering insights on potential modifications to the joint development process, all from the viewpoint of stakeholders. Design This qualitative study employed one-to-one semi-structured interviews, and the findings were analysed using summarising qualitative content analysis. Setting The study focused on the German healthcare system. Participants Seven stakeholders from the coproduction process were purposefully selected for interviews using maximum variation sampling. The interviewees represented different sectors (physician associations, physical activity professionals' associations, health insurance companies and patient organisations), various positions within their organisations, and different levels of attendance during the coproduction process. Results In almost all interviews, the following factors were highlighted as facilitators of the development process: coproduction approach, process of coproduction, multi-sector stakeholder group, possibility of active participation, coordinating role of researchers, communication, atmosphere and interaction. In contrast, differences in roles and hierarchy, merging of different perspectives, clarification of intervention costs, and competition and conflicting interests were pointed out as challenges. Only a few suggestions regarding adaptations in terms of group composition and cooperation among stakeholders were mentioned. Conclusions Stakeholder experiences with the joint development process were predominantly positive, indicating that coproduction is a beneficial approach for the development of PARS intended for integration into healthcare systems. The effective management of power differences among stakeholders is intricately tied to the coproduction method; therefore, it should be selected carefully. The research team plays a pivotal role in coordinating and negotiating the process, and the team should be equipped with a diverse set of skills and knowledge, particularly to understand the intricacies of the healthcare system where the PARS is intended for implementation. Trial registration number NCT04947787.
CRIS-Team Scopus Importer:2024-05-31
Keywords: health services; patient participation; primary health care; qualitative research

Co-production of a physical activity referral scheme in the German healthcare system - Geidl, Wolfgang; Klamroth, Sarah; Mino, Eriselda; Weißenfels, Anja; Naber, Inga; Gelius, Peter; Abu-Omar, Karim; Pfeifer, Klaus (International Society for Physical Activity and Health (ISPAH) Congress 2024, 2024)
Background: Physical activity referral schemes (PARS) have the potential to promote physical activity (PA) among the mostly inactive primary care population with non-communicable diseases (NCD). No PARS has yet been structurally implemented in the German primary care system. Purpose: The research project BewegtVersorgt aims to develop, implement and evaluate a PARS to promote PA for persons with NCD within the German healthcare system. Methods: The PARS was developed using a co-production approach which integrated twelve organizations from different sectors (health insurances, physicians, exercise professionals, patients’ representatives). Three co-production meetings were applied where individual ideas and current evidence were combined, and different PARS models were elaborated. Finally, all stakeholders agreed on one PARS for implementation as a regional model project and seven stakeholders were purposefully selected for interviews to evaluate the co-production process. Results: The co-produced PARS starts with the primary care physician who offers PA advice and afterward refers patients to an exercise professional. The exercise professional delivers the remaining components of the intervention: initial assessment, six 1-hour individual PA counselling sessions, final assessment. From stakeholder perspective, the following factors were highlighted as facilitators of the development process: co-production approach, process of co-production, multi-sector stakeholder group, possibility of active participation, coordinating role of researchers, communication, atmosphere and interaction. In contrast, differences in roles and hierarchy, merging of different perspectives, clarification of intervention costs, and competition and conflicting interests were pointed out as challenges. Conclusions: By using the co-production approach, it was possible to develop a new PARS and implement it as regional model project in routine practice. Practical implications: Co-production is a beneficial approach for the development of PARS intended for integration into healthcare systems. Support/Funding Source: The study is funded by the Federal Ministry of Health based on a resolution of the German ‘Bundestag’ by the federal governmen

Co-production of a physical activity referral scheme in the German health care system - Mino, Eriselda; Klamroth, Sarah; Weißenfels, Anja; Naber, Inga; Geidl, Wolfgang; Gelius, Peter; Abu-Omar, Karim; Pfeifer, Klaus (HEPA Europe, 2023)
Purpose Physical activity referral schemes (PARS) have the potential to promote physical activity (PA) among the mostly inactive primary care population with non-communicable diseases (NCD). Despite significant expansion throughout Europe, a national scheme has not yet been established in Germany. Thus, the ongoing research project BewegtVersorgt aims to develop, implement, and evaluate a PARS to promote PA for persons with NCD within the German healthcare system. Methods The PARS was developed using a co-production approach which integrated twelve organizations from different sectors within the healthcare system (health insurances, physicians, exercise professionals, patients’ representatives) and was guided by the research team. Initially, stakeholders’ ideas of a PARS were collected in individual interviews. These were followed by three co-production meetings where individual ideas and current evidence were combined, and different PARS models for the German setting were elaborated. Finally, all stakeholders agreed on one PARS for implementation as a regional model project. Results The co-produced PARS starts with the primary care physician, as the gatekeeper in the German healthcare system, who offers 10 min PA advice to the patients who would benefit from PA participation. Afterward, the patients are referred to an exercise professional through a referral form. The exercise professional delivers the remaining central components of the intervention - initial assessment, six 1-hour individual PA counseling sessions spread throughout 12 weeks, final assessment, a progress report to the general practitioner, and one follow-up visit at six months. The intervention uses a patient-centered approach and motivational interviewing. The end goal is an adaptation of an active lifestyle and transfer to local physical activity opportunities. Conclusions By using a co-production approach, the expertise of different stakeholders within the healthcare system as well as scientific findings could be integrated into the development process of the PARS. To which extent this participatory approach leads to greater acceptance of the new healthcare service among the implementing actors and positively influences their cooperation within the PARS will be evaluated during the implementation phase. Support/Funding Source The study is funded by the Federal Ministry of Health based on a resolution of the German ‘Bundestag’ by the federal government.

Coproduction to improve preventive health services—experiences from Germany - Abu-Omar, Karim; Weißenfels, Anja; Mino, Eriselda; Naber, Inga; Klamroth, Sarah; Geidl, Wolfgang; Pfeifer, Klaus (Health promotion international, 2021)
Due to the beneficial impact of regular physical activity (PA) on non-communicable diseases, the number of countries integrating exercise referral schemes (ERSs) into their healthcare systems is growing. Owing to the limitations of existing PA promotion concepts in Germany’s healthcare system, efforts are currently being made towards developing a nationwide referral pathway. A research group at the Friedrich-Alexander-University Erlangen-Nürnberg is coordinating these efforts within a project funded by the Federal Ministry of Health. The aim is to develop, implement and evaluate a regional-level ERS that has the potential to be scaled up across Germany in the event of its demonstrated effectiveness. The project is based on an adapted Cooperative Planning approach requiring interaction between the academic sector and different actors of the healthcare sector. The present commentary reflects on challenges faced in the early stages of the co-production process. Besides the development of an adequate co-production methodology, it critically discusses stakeholder participation, knowledge gaps and actors’ willingness to take responsibility. In addition, although patients are represented by dedicated organizations, their perspective cannot be adequately captured using a co-production approach. Despite the joint development of an ERS, there remain important questions regarding the appropriateness of the co-production approach in a healthcare setting.
Keywords: physical activity promotion; exercise referral scheme; co-production process; non-communicable diseases; primary healthcare

Development, implementation, evaluation and scaling-up of physical activity referral schemes in Germany: protocol for a study using a co-production approach - Weißenfels, Anja; Geidl, Wolfgang; Mino, Eriselda; Naber, Inga; Klamroth, Sarah; Gelius, Peter; Abu-Omar, Karim; Pfeifer, Klaus (BMJ Open, 2021)
Introduction Physical activity referral schemes (PARSs) are recommended to promote physical activity (PA) among adults at risk of developing or with established non-communicable diseases (NCDs). In Germany, this kind of referral schemes has not yet been implemented systematically and nationwide. In this study protocol, we present the methodological design of a co-production research study aimed at establishing a PARS for adults with NCDs in German primary healthcare. Methods and analysis We will employ a co-production approach consistently throughout the four project phases: (1) development of the PARS; (2) preparation period; (3) implementation and evaluation; (4) development of a strategic plan for scaling up the PARS to the national level as part of standard care. The first phase will additionally include a status quo analysis of the existing physical activity pathways nationwide as well as an overview of international PARS models. A pragmatic trial design will be used for evaluating the developed PARS. The co-production approach will involve relevant actors in the German healthcare system, namely, healthcare service providers (eg, physicians, exercise professionals), health insurance providers, exercise providers, patients’ representatives, experts in the development and implementation of educational concepts, and scientists from the fields of sports science and public health. Ethics and dissemination The project has been reviewed and approved by the ethics committee of the Friedrich-Alexander-University Erlangen-Nürnberg (ethics approval number: 331_20 B). Through cooperation agreements, the stakeholders involved gave their consent to participate and were informed about the study in detail. The results of this study will be disseminated by international conference presentations and peer-reviewed publications, and if possible, a manual for the use of the PARS will be provided.

Die Wirksamkeit bewegungstherapeutischer Maßnahmen auf die posturale Instabilität bei Morbus Parkinson: Eine Metaanalyse - Klamroth, Sarah; Steib, Simon; Devan, Surendar; Pfeifer, Klaus (Moving Minds - Crossing Boundaries in Sport Science, 2015)

Drop-out-Analysen in einer pragmatischen Implementierungsstudie zur Bewegungsförderung im deutschen Gesundheitssystem - Mino, Eriselda; Klamroth, Sarah; Weißenfels, Anja; Naber, Inga; Geidl, Wolfgang; Gelius, Peter; Pfeifer, Klaus (Abstractband, 2024)
Einleitung Drop-out-Analysen in Interventionsstudien spielen im Zusammenhang mit der Förderung der Motivation für körperliche Aktivität bei Menschen mit chronischen nichtübertragbaren Erkrankungen (NCD) eine wichtige Rolle. Im Projekt BewegtVersorgt wurde in einer pragmatischen Implementierungsstudie (02/2022-12/2023) eine neue Bewegungsversorgungskette (PARS: ärztliche Kurzberatung und individuelle Bewegungsförderung durch Therapeut*innen) mit einer alleinigen strukturierten ärztlichen Kurzberatung (PAA) verglichen. Das Ziel der vorliegenden Studie ist die Analyse der Drop-out Faktoren für beide Interventionsformen. Methode Die Drop-out-Analyse wurde mittels binärer logistischer Regressionen durchgeführt (SPSS 29.0). Die Teilnehmercharakteristika zu Studienbeginn wurden dabei als unabhängige Prädiktoren integriert. Zusätzlich wurden die Teilnehmenden telefonisch mittels strukturiertem Gesprächsleitfaden zu den Gründen des Studienabbruchs befragt. Ergebnisse Von insgesamt 168 Studienteilnehmenden (PARS n=109; PAA n=59) haben 54,1 % (PARS) und 47,5 % (PAA) die Intervention abgebrochen, ohne signifikanten Unterschied zwischen den Gruppen. In der PARS-Gruppe erhöhte das Vorliegen einer koronaren Herzkrankheit die Drop-out-Wahrscheinlichkeit um den Faktor 4,3 (95%KI: 1,2-15,6; R2: 0,127). In der PAA-Gruppe war die Drop-out-Rate bei Männern 4,1-mal höher als bei Frauen (95%KI: 1,3-12,3; R2: 0,135), ein Trend der sich auch bei PARS abzeichnete (p=0,058). Bei der telefonischen Befragung der Drop-out-Gründe wurden bei PARS gesundheitliche Probleme (24%) und bei PAA mangelnde Fragebogen-Compliance (36%) sowie andere Prioritäten (PARS 17%; PAA 14%) am häufigsten berichtet. Diskussion Die vorliegenden Ergebnisse liefern relevante Erkenntnisse für die Bewegungsförderung von Personen mit NCD in der Gesundheitsversorgung. Der Einfluss der Corona-Pandemie auf diese Implementierungsstudie ist vor dem Hintergrund der Überlastung des Gesundheitssystems, eingeschränkter regionaler Bewegungsangebote und gesundheitlicher Einschränkungen der Teilnehmenden besonders zu berücksichtige
Keywords: Bewegungsförderung; Gesundheitsversorgung; Menschen mit chronischen nichtübertragbaren Erkrankungen; Drop-out Faktoren

Effectiveness and implementation success of a co-produced physical activity referral scheme in Germany: study protocol of a pragmatic cluster randomised trial - Weißenfels, Anja; Klamroth, Sarah; Carl, Johannes; Naber, Inga; Mino, Eriselda; Geidl, Wolfgang; Gelius, Peter; Abu-Omar, Karim; Pfeifer, Klaus (BMC Public Health, 2022)
Background While effective physical activity referral schemes (PARSs) and related structures for promoting physical activity (PA) already exist in several countries, in Germany, PARSs have not yet been implemented systematically and nationwide. Through a co-production approach with relevant actors in the German healthcare system, a PARS was developed, and an implementation plan was created (e.g. financing). This study protocol aims to evaluate the developed PARS for people with non-communicable diseases (NCDs) in Germany regarding its potential effectiveness and implementation success. Methods To evaluate the effectiveness and implementation success of the PARS, we will apply a pragmatic cluster-randomised controlled trial (cRCT) in Hybrid II design by comparing two intervention groups (PARS vs PA advice [PAA]). The trial will take place in the Nürnberg metropolitan region, with 24 physician practices recruiting 567 people with NCDs. Both groups will receive brief PA advice from a physician to initially increase the participants’ motivation to change their activity level. Subsequently, the PARS group will be given individualised support from an exercise professional to increase their PA levels and be transferred to local exercise opportunities. In contrast, participants in the PAA group will receive only the brief PA advice as well as information and an overview of regional PA offerings to become more active at their own initiative. After 12 and 24 weeks, changes in moderate to vigorous PA and in physical activity-related health competence (movement competence, control competence, self-regulation competence) will be measured as primary outcomes. Secondary outcomes will include changes in quality of life. To measure implementation success, we refer to the RE-AIM framework and draw on patient documentation, interviews, focus groups and surveys of the participating actors (physicians, exercise professionals). Discussion Through a between-group comparison, we will investigate whether additional individual support by an exercise professional compared to brief PA advice alone leads to higher PA levels in people with NCDs. The acceptance and feasibility of both interventions in routine care in the German healthcare system will also be evaluate
CRIS-Team WoS Importer:2022-08-26

Effects of perturbed treadmill training on Parkinsonian gait: time-course, sustainability, and transfer effects - Steib, Simon; Klamroth, Sarah; Gaßner, Heiko; Pasluosta, Cristian Federico; Eskofier, Björn; Winkler, Jürgen; Klucken, Jochen; Pfeifer, Klaus (Sportmotorik 2019. Adaptation, Lernen und virtuelle Welten. Abstractband zur 16. Jahrestagung der dvs-Sektion Sportmotorik vom 16.-18. Januar 2019 in Bern, 2019)

Empfehlungen für Bewegung - Pfeifer, Klaus; Banzer, Winfried; Ferrari, Nina; Füzéki, Eszter; Geidl, Wolfgang; Graf, Christine; Hartung, Verena; Klamroth, Sarah; Völker, Klaus; Vogt, Lutz (Nationale Empfehlungen für Bewegung und Bewegungsförderung, 2016)
Die Nationalen Empfehlungen für Bewegung und Bewegungsförderung wurden von einer Gruppe von Wissenschaftlerinnen und Wissenschaftlern erarbeitet und haben das Ziel, eine wissenschaftliche Orientierung im Feld der Bewegungsförderung zu bieten. Sie richten sich primär an Fachleute, Entscheidungsträger und Multiplikatoren.

Erfahrungen mit der Koproduktion einer Bewegungsversorgungskette: Eine qualitative Auswertung von Stakeholder-Interviews - Klamroth, Sarah; Mino, Eriselda; Naber, Inga; Weißenfels, Anja; Geidl, Wolfgang; Gelius, Peter; Abu-Omar, Karim; Pfeifer, Klaus (Schriften der Deutschen vereinigung für Sportwissenschaft, 2023)

Etablierung von Versorgungsketten zur Bewegungsförderung für Menschen mit nichtübertragbaren Erkrankungen – ein partizipativer Ansatz im Projekt BewegtVersorgt - Naber, Inga; Weißenfels, Anja; Klamroth, Sarah; Mino, Eriselda; Geidl, Wolfgang; Gelius, Peter; Abu-Omar, Karim; Pfeifer, Klaus (19. Deutscher Kongress für Versorgungsforschung, 2020)
Hintergrund und Stand internationaler Forschung: Bewegungsversorgungsketten (BVK) sind in vielen Ländern (z.B. Neuseeland) bereits fest in die Routinepraxis der Gesundheitssysteme eingebettet und zeigen nachhaltige Steigerungen körperlicher Aktivität bei Menschen mit nichtübertragbaren Erkrankungen (NCD) [1]. Zwar befürworten auch nationale Empfehlungen eine ärztlich initiierte Bewegungsversorgung [2], die vorhandenen BVK zielen bislang vornehmlich auf die Verbesserung von Körperfunktionen, weniger auf Bewegungsförderung ab. Fragestellung und Zielsetzung: Vor dem Hintergrund vorliegender Evidenz stellt sich für Deutschland die Frage, wie verhaltensbezogene Bewegungsförderung in BVK integrieren werden kann. Das Ziel des Projekts BewegtVersorgt (im Förderschwerpunkt Bewegung und Bewegungsförderung des BMG) ist es, über einen partizipativen Ansatz BVK für Menschen mit NCD zu entwickeln, auf regionaler Ebene zu erproben und nach positiver Evaluation einen Transfer in die nationale Regelversorgung vorzubereiten. Methode: Zur Erreichung des Projektziels in Phase 1 wurde, ebenso wie im gesamten Projektverlauf, ein Co-Creation Ansatz mit Akteuren des Gesundheitssystems (Kostenträger, Ärzte, Patientenvertretung, Leistungserbringer/Bewegungsanbieter) verfolgt. Der Entwicklungsprozess beinhaltete 1. qualitative Interviews mit den Projektpartnern über Hindernisse/Förderfaktoren und ihre eigene Rolle in der Umsetzung von BVK, 2. systematische Literaturrecherche zur Identifizierung von Kernelementen sowie 3.drei Planungstreffen zur partizipativen Entwicklung möglicher BVK unter Einbeziehung der eruierten Kernelemente. Ergebnisse: In der ersten Projektphase wurden sieben int. Kernelemente als Teil der BVK identifiziert: Assessment, Beratung, schriftliche und verbindliche Verordnung, individualisierte Bewegungsempfehlungen, Verhaltensänderungstechniken, unterstützende Person, Follow-up. Gute Kommunikation zwischen den Akteuren sowie konstruktives Feedback wurden als Förderfaktoren identifiziert. Entsprechend wurden in den partizipativen Planungstreffen Schwimmbahnmodelle für potenzielle BVK für Deutschland entwickelt. Diskussion: Die Nutzung des Co-Creation-Ansatzes ermöglichte die konsensuale Einigung auf Varianten einer BVK. Der fortlaufende partizipative Prozess sowie das Überwinden von möglichen Barrieren werden eine kontinuierliche Anpassung der BVK erfordern. Die Wirksamkeit sowie die Kosten-Effektivität der BVK müssen im nächsten Schritt pilotartig erprobt und evaluiert werden. Praktische Implikationen: Das partizipative Vorgehen unter Beteiligung relevanter Akteure erhöht die Chancen der Akzeptanz und nachhaltigen Implementierung der BVK. Basierend auf den Evaluationsergebnissen der Umsetzungsphase wird ein Disseminierungskonzept zum Transfer in die bundesweite Regelversorgung erstellt.

Exploring gait adaptations to perturbed and conventional treadmill training in Parkinson’s disease: Time-course, sustainability, and transfer - Steib, Simon; Klamroth, Sarah; Gaßner, Heiko; Pasluosta, Cristian Federico; Eskofier, Björn; Winkler, Jürgen; Klucken, Jochen; Pfeifer, Klaus (Human Movement Science, 2019)

Förderung von bewegungsbezogener Gesundheitskompetenz in ärztlich verordneten Bewegungsinterventionen – Aufbau des Interventionskonzeptes im Forschungsprojekt BewegtVersorgt. - Naber, Inga; Klamroth, Sarah; Weißenfels, Anja; Geidl, Wolfgang; Streber, René; Mino, Eriselda; Gelius, Peter; Abu-Omar, Karim; Pfeifer, Klaus (Bewegungstherapie und Gesundheitssport, 2022)
Die ärztlich-initiierte Verordnung von Bewegung kann als effektive Methode zur Bewegungsförderung von Menschen mit nichtübertragbaren Erkrankungen (non-communicable diseases – NCD) eingesetzt werden. Die Förderung der bewegungsbezogenen Gesundheitskompetenz (BGK) im Rahmen der verordneten Bewegung beeinfl usst die Gesundheitswirkungen, den Bewältigungsprozess sowie das Bewegungsverhalten positiv. In diesem Artikel wird ein BGK-basiertes Interventionskonzept zur ärztlich-initiierten Bewegungsförderung vorgestellt, welches im Projekt BewegtVersorgt entwickelt wurde. Das Forschungsprojekt BewegtVersorgt hat das Ziel, in Deutschland eine solche ärztlich-initiierte Bewegungsversorgungskette zur systematischen Bewegungsförderung für Menschen mit NCD zu entwickeln, zu erproben und zu evaluieren. Im Rahmen des Projekts haben sich zwölf Organisationen aus unterschiedlichen Bereichen des Gesundheitssystems (Ärzteschaft, Kostenträger, Bewegungsanbieter, Vertretung der Betroff enen) an der Entwicklung einer Bewegungsversorgungskette beteiligt. Diese Versorgungskette wird in Form eines Modellprojektes nach §§ 63 Abs. 2, 64 SGB V gemeinsam mit ärztlichem Fachpersonal, Bewegungsfachpersonal und Bewegungsanbietern in der Routineversorgung für ein Jahr erprobt. Die Kernkomponente der Bewegungsversorgungskette stellt die individuelle Bewegungsförderung (IBF) dar, welche basierend auf dem Modell der BGK entwickelt wurde und von speziell geschultem Bewegungsfachpersonal durchgeführt wird. Das Konzept ist modular aufgebaut, integriert spezifi sche Methoden sowie Arbeitsmaterialien und umfasst eine 1:1 Betreuung über einen Zeitraum von 24 Wochen (6 Einheiten à 60 Minuten und drei Assessments). Nach der Erprobung werden der Implementierungserfolg in der Routineversorgung sowie die Wirksamkeit der Versorgungskette im Hinblick auf die Steigerung des körperlichen Aktivitätslevels und der BGK evaluiert. Sollte sich das neue Versorgungskonzept als wirksam erweisen, ist für die letzte Projektphase die Entwicklung eines Transfer- und Skalierungskonzepts zur nachhaltigen Verankerung in der Gesundheitsversorgung geplant.<br
Keywords: Körperliche Aktivität; ärztlich-initiierte Bewegungsförderung; Versorgungsstrukturen; individuelle Bewegungsförderung; bewegungsbezogene Gesundheitskompetenz

Gait adaptations to treadmill training in Parkinson’s patients: effects of perturbation, sustainability, and moderators - Steib, Simon; Klamroth, Sarah; Gaßner, Heiko; Pasluosta, C. F.; Eskofier, Björn; Winkler, Jürgen; Klucken, Jochen; Pfeifer, Klaus (Book of Abstracts, 2018)

Immediate effects of perturbation treadmill training on gait and postural control in patients with Parkinson’s disease - Klamroth, Sarah; Steib, Simon; Gaßner, Heiko; Goßler, Julia; Winkler, Jürgen; Eskofier, Björn; Klucken, Jochen; Pfeifer, Klaus (Gait & Posture, 2016)
EVALuna2:33512

Implementation of a physical activity referral scheme in the German healthcare system: A qualitative analysis of implementation success - Klamroth, Sarah; Lorenz, Eva; Naber, Inga; Mino, Eriselda; Weißenfels, Anja; Geidl, Wolfgang; Gelius, Peter; Abu-Omar, Karim; Pfeifer, Klaus (15th conference of HEPA Europe "Optimising health enhancing physical activity: the importance of inclusion", 2024)

Implementation success of a physical activity referral scheme (PARS) in the German healthcare system - Klamroth, Sarah; Lorenz, Eva; Naber, Inga; Mino, Eriselda; Weißenfels, Anja; Geidl, Wolfgang; Gelius, Peter; Abu-Omar, Karim; Pfeifer, Klaus (10th ISPAH Congress "Accelerating policy and practice to ensure physical activity for all", 2024)

Implementierung bewegungsbezogener Interventionen in der Routine-versorgung: Erfahrungen aus dem Forschungsprojekt BewegtVersorgt - Klamroth, Sarah; Weißenfels, Anja; Mino, Eriselda; Naber, Inga; Geidl, Wolfgang; Gelius, Peter; Abu-Omar, Karim; Pfeifer, Klaus (Jahrestagung der dvs-Kommission Gesundheit, 2022)

Implementierungserfolg einer Bewegungsversorgungskette im deutschen Gesundheitssystem: Eine qualitative Analyse aus der Perspektive von Ärzt*innen und Bewegungstherapeut*innen - Klamroth, Sarah; Lorenz, Eva; Naber, Inga; Mino, Eriselda; Weißenfels, Anja; Geidl, Wolfgang; Gelius, Peter; Abu-Omar, Karim; Pfeifer, Klaus (Jahrestagung der dvs-Kommission Gesundheit "Sport, Bewegung und Ernährung - unzertrennlich für einen gesunden Lebensstil?", 2024)

Individuelle Therapieeffekte: Analyse interindividueller Unterschiede in der Anpassung der Gleichgewichtsfähigkeit nach Laufbandtherapie bei Parkinsonpatienten - Klamroth, Sarah; Gaßner, Heiko; Winkler, Jürgen; Eskofier, Björn; Klucken, Jochen; Pfeifer, Klaus; Steib, Simon (3. Symposium Physiotherapiewissenschaft, 2018)

Interindividual Balance Adaptations in Response to Perturbation Treadmill Training in Persons With Parkinson Disease - Klamroth, Sarah; Gaßner, Heiko; Winkler, Jürgen; Eskofier, Björn; Klucken, Jochen; Pfeifer, Klaus; Steib, Simon (Journal of Neurologic Physical Therapy, 2019)
BACKGROUND AND PURPOSE: Perturbation training is a promising approach to reduce fall incidence in persons with Parkinson disease (PwPD). This study aimed to evaluate interindividual differences in balance adaptations in response to perturbation treadmill training (PTT) and identify potential outcome predictors. METHODS: PwPD (n = 43, Hoehn & Yahr stage 1-3.5) were randomly assigned to either 8 weeks of PTT or conventional treadmill training (CTT) without perturbations. At baseline and following intervention, data from 4 domains of balance function (reactive, anticipatory, dynamic postural control, and quiet stance) were collected. Using responder analysis we investigated interindividual differences (responder rates and magnitude of change) and potential predictive factors. RESULTS: PTT showed a significantly higher responder rate in the Mini Balance Evaluation Systems Test (Mini-BESTest) subscore reactive postural control, compared with CTT (PTT = 44%; CTT = 10%; risk ratio = 4.22, confidence interval = 1.03-17.28). Additionally, while between-groups differences were not significant, the proportion of responders in the measures of dynamic postural control was higher for PTT compared with CTT (PTT: 22%-39%; CTT: 5%-10%). The magnitude of change in responders and nonresponders was similar in both groups. PTT responders showed significantly lower initial balance performance (4/8 measures) and cognitive function (3/8 measures), and were older and at a more advanced disease stage, based on descriptive evaluation. DISCUSSION AND CONCLUSIONS: Our findings suggest that PTT is beneficial to improve reactive balance in PwPD. Further, PTT appeared to be effective only for a part of PwPD, especially for those with lower balance and cognitive function, which needs further attention.Video Abstract available for more insights from the authors (see the Video, Supplemental Digital Content 1, http://links.lww.com/JNPT/A1).
CRIS-Team Scopus Importer:2019-09-20

Koproduktion und Implementierung einer Bewegungsversorgungskette für Menschen mit nichtübertragbaren Erkrankungen: Projekt BewegtVersorgt - Pfeifer, Klaus; Weißenfels, Anja; Klamroth, Sarah; Naber, Inga; Mino, Eriselda; Geidl, Wolfgang; Gelius, Peter; Abu-Omar, Karim (22. Deutscher Kongress für Versorgungsforschung, 2023)

Koproduktion und Implementierung von Ärztlich-initiierter Bewegungsförderung für Menschen mit nichtübertragbaren Erkrankungen - Weißenfels, Anja; Klamroth, Sarah; Naber, Inga; Mino, Eriselda; Geidl, Wolfgang; Gelius, Peter; Abu-Omar, Karim; Pfeifer, Klaus (Sports, Medicine and Health Summit 2023, 2023)

Laufbandtherapie in der Neurorehabilitation: Evidenz und Anwendungsspektrum - Klamroth, Sarah; Gaßner, Heiko; Winkler, Jürgen; Eskofier, Björn; Klucken, Jochen; Pfeifer, Klaus; Steib, Simon (Neurologie & Rehabilitation, 2018)

Laufbandtraining mit Perturbation verbessert Gang- und Gleichgewichtskontrolle bein Parkinsonpatienten: Eine randomisiert-kontrollierte Pilotstudie - Steib, Simon; Klamroth, Sarah; Gaßner, Heiko; Pasluosta, Cristian Federico; Eskofier, Björn; Winkler, Jürgen; Klucken, Jochen; Pfeifer, Klaus (Innovation & Technologie im Sport. Abstractband des 23. dvs-Hochschultags vom 13. bis 15. September 2017 in München, 2017)
Keywords: Morbus Parkinson; Laufbandtraining; Gehfähigkeit; Balance

Motor Output Complexity in Parkinson's disease Patients during Acute Treadmill Intervention - Pasluosta, Cristian Federico; Steib, Simon; Klamroth, Sarah; Gaßner, Heiko; Hannink, Julius; Von Tscharner, Vinzenz; Pfeifer, Klaus; Winkler, Jürgen; Klucken, Jochen; Eskofier, Björn (International Symposium on the Neuromechanics of Human Movement, 2016)

National Recommendations for Physical Activity - Pfeifer, Klaus; Banzer, Winfried; Ferrari, Nina; Füzéki, Eszter; Geidl, Wolfgang; Graf, Christine; Hartung, Verena; Klamroth, Sarah; Völker, Klaus; Vogt, Lutz (National Recommendations for Physical Activity and Physical Activity Promotion, 2016)
The National Recommendations for Physical Activity and Physical Activity Promotion target experts and stakeholders. The recommendations have been developed for Germany, but may also apply to other countries. They were created by a group of scientists and aim to offer a scientic orientation in the field of physical activity promotion.

Neue Ansätze in der Bewegungstherapie bei Morbus Parkinson - Wanner, Philipp; Klamroth, Sarah; Steib, Simon (Zeitschrift für Gerontologie und Geriatrie, 2022)
Background: Exercise therapy is an important component in the treatment of motor symptoms in people with Parkinson’s disease (PD). In this context, goal-based task-specific training has shown to be particularly effective compared to nonspecific approaches. Objective: In this article two novel exercise interventions for targeted improvement of motor function in PD are presented: 1) task-specific training with perturbations and 2) combined task-specific and cardiovascular training. Material and methods: Summary and discussion of the current evidence for both therapeutic approaches. Results: First randomized controlled trials show that perturbation training is an effective task-specific training to improve gait and balance function and potentially reduce falls. Experimental findings on combined cardiovascular exercise and task-specific training suggest that processes of neuroplasticity are enhanced, thereby improving therapy outcomes. However, the quality of evidence for both therapeutic approaches is currently low. Conclusion: The presented exercise approaches show promising results in first randomized controlled studies and have the potential to improve treatment outcomes in PD. Further high-quality clinical studies are needed to ensure an effective transfer into practice.
CRIS-Team Scopus Importer:2022-11-25
Keywords: Cardiovascular exercise; Gait; Motor learning; Parkinson’s disease; Perturbation training; Postural control

P07-04 A systematic review of key interventional elements in international exercise referral schemes - Mino, Eriselda; Hanson, Coral; Geidl, Wolfgang; Naber, Inga; Mchale, Sheona; Klamroth, Sarah; Weißenfels, Anja; Gelius, Peter; Abu-Omar, Karim; Pfeifer, Klaus (European Journal of Public Health, Volume 32, Issue Supplement_2, 2022)
Background With the first initiatives dating back to the 1990s, the past two decades have seen a rapid increase in the use of exercise referral schemes (ERS) worldwide. Despite the accumulating evidence on their effectiveness, there are currently no international guidelines available to inform the design of such interventions. The key elements and processes employed vary both within and between countries. This systematic review aims to address this frequently overlooked topic by identifying elements that are predominant in international ERS. Methods Scientific databases (PubMed, Scopus) and grey literature sources were systematically searched. In order to collect the information relevant for understanding and visualizing all ERS models, a broad spectrum of document types was considered eligible for inclusion, i.e. randomized controlled or pragmatic trials, cohort studies, case-control studies, case series, case reports, qualitative studies, economic evaluations, mixed designs, policy documents, and official governmental reports. We extracted data on scheme components, contents, and main actors involved in scheme delivery. Cross-functional flowcharts were employed to facilitate comparison between different ERS designs: Firstly, the collected data were visualized in flowcharts indicating the pathway a patient follows from beginning to end of an individual ERS. Secondly, elements that appeared more frequently across all included ERS were identified. Results Preliminary results identified 18 models of ERS that were eligible for data analysis, including Green Prescription (New Zealand), Hreyfiseðill (Iceland), National Exercise Referral Scheme (Wales). Program designs ranged from short advice by a primary healthcare professional to physical activity prescription and/or further referral to affiliated health professionals. The prevailing actors involved in scheme delivery were physicians, nurses, physiotherapists, training experts, physical activity providers, and coordinators. Seven predominant elements emerged from the comparison between ERS designs: assessment, counselling, individualized physical activity recommendations, written prescription, behavior change techniques, support person, and follow-up. Conclusions To the best of our knowledge, this is the first study that takes a closer look at the design characteristics of ERS across the world. Our preliminary results indicate that there are seven key elements. The contribution of these elements on the effectiveness of ERS needs to be explored in future research.
Keywords: exercise referral scheme; exercise prescription; physical activity on prescription scheme; physical activity promotion; primary health care

P07-11 Physical activity promotion in the German healthcare system-Establishing pathways of exercise referral for persons with noncommunicable diseases - Klamroth, Sarah; Naber, Inga; Mino, Eriselda; Geidl, Wolfgang; Gelius, Peter; Abu-Omar, Karim; Pfeifer, Klaus (EUROPEAN JOURNAL OF PUBLIC HEALTH, 2022)
CRIS-Team WoS Importer:2022-09-23

P07-12 Stakeholders perspectives on exercise referral schemes in Germany - Naber, Inga; Mino, Eriselda; Klamroth, Sarah; Weißenfels, Anja; Geidl, Wolfgang; Gelius, Peter; Abu-Omar, Karim; Pfeifer, Klaus (2022)
Background There is a growing popularity of exercise referral schemes (ERS) and they are widely implemented in nations such as New Zealand and Sweden. To this point, the German health care system (GHCS) is not utilising a structurally implemented ERS, but a research project is currently conducted to develop and test a German ERS. In the first project phase, the aim was to introduce the topic of ERS to relevant stakeholders of the GHCS and to gather their expert opinions on such a potential ERS. Further, the aim was to familiarise the stakeholders to the project and its collaborative approach in developing and testing an ERS. Methods Semi-structured interviews were conducted with 12 relevant stakeholder of the GHCS. In each case, two researchers conducted the interviews between June to September 2019. Main topics addressed during the interviews were potential target groups for an ERS, their own role within an ERS, PA counselling and dropouts that would be expected. During the interviews, stakeholders were encouraged to sketch their ideas for how to organise an ERS on paper. In the analysis, we digitalised these sketches into flow-chart diagrams. Results The analysis of the interviews showed that the sketches proposed innovative additions and alternative PA promotion strategies within the GHCS. The stakeholders identified barriers within the GHCS such as the rigid costing of treatments and performance measurements. Some reoccurring important core elements for an ERS in Germany were suggested: having a supportive person, implementing PA behaviour impact, utilising existing PA programs and tailoring individual PA counselling. Some stakeholders envisioned an ERS focusing on their perspectives and desired role within the ERS while others outlined ERS that largely excluded them. Conclusions All stakeholders clearly expressed the need for collaboration to develop and test an ERS in Germany. Previous studies have been focused on factors that influence effectiveness, as uptake and adherence. In contrast, these interviews resulted in the identification of concrete barriers and facilitators from the administrative perspective within the GHCS. Different stakeholders show varying degrees of interest in being part of an ERS. This information is highly valuable for the upcoming collaborative process.
Keywords: exercise referral; physical activity promotion; primary healthcare; participatory research approach; physical activity on prescription

Perturbation during treadmill training improves dynamic balance and gait in Parkinson’s disease: A single-blind randomized controlled pilot trial - Steib, Simon; Klamroth, Sarah; Gaßner, Heiko; Pasluosta, Cristian Federico; Eskofier, Björn; Winkler, Jürgen; Klucken, Jochen; Pfeifer, Klaus (Neurorehabilitation and Neural Repair, 2017)

Perturbation Treadmill Training Improves Clinical Characteristics of Gait and Balance in Parkinson's Disease - Gaßner, Heiko; Steib, Simon; Klamroth, Sarah; Pasluosta, Cristian Federico; Adler, Werner; Eskofier, Björn; Pfeifer, Klaus; Winkler, Jürgen; Klucken, Jochen (Journal of Parkinson's Disease, 2019)
Background: Impaired gait and postural stability are cardinal motor symptoms in Parkinson's disease (PD). Treadmill training improves gait characteristics in PD. Objective: This study investigates if postural perturbations during treadmill training improve motor performance and particularly gait and postural stability in PD. Methods: This work presents secondary outcome measures of a pilot randomized controlled trial. PD patients (n=43) recruited at the University Hospital Erlangen were randomly allocated to the experimental (perturbation treadmill training, PTT, n=21) or control group (conventional treadmill training, CTT, n=22). Outcome measures were collected at baseline, after 8 weeks of intervention, and 3 months follow-up. Motor impairment was assessed by the Unified Parkinson Disease Rating Scale part-III (UPDRS-III), Postural Instability and Gait Difficulty score (PIGD), and subitems 'Gait' and 'Postural stability' by an observer blinded to the randomization. Intervention effects were additionally compared to progression rates of a matched PD cohort (n=20) receiving best medical treatment (BMT). Results: Treadmill training significantly improved UPDRS-III motor symptoms in both groups with larger effect sizes for PTT (-38%) compared to CTT (-20%). In the PTT group solely, PIGD -34%, and items 'Gait' -50%, and 'Postural stability' -40% improved significantly in comparison to CTT (PIGD -24%, 'Gait' -22%, 'Postural stability' -33%). Positive effects persisted in PTT after 3 months and appeared to be beneficial compared to BMT. Conclusions: Eight weeks of PTT showed superior improvements of motor symptoms, particularly gait and postural stability. Sustainable effects indicate that PTT may be an additive therapy option for gait and balance deficits in PD.
CRIS-Team Scopus Importer:2019-06-18
Keywords: Gait analysis; Parkinson's disease; postural stability; treadmill training

Perturbation Treadmill Training in Parkinson's Disease: A Novel Approach for Neurological Rehabilitation - Klamroth, Sarah (Springer, 2018)

Perturbation Treadmill Training – Introducing Postural Challenge and Practice Variability in Gait Rehabilitation of Parkinson’s Patients - Steib, Simon; Klamroth, Sarah; Gaßner, Heiko; Goßler, Julia; Winkler, Jürgen; Eskofier, Björn; Klucken, Jochen; Pfeifer, Klaus (Human Movement and Technology, 2016)

Physical activity referral scheme components: a study protocol for systematic review and meta-regression - Mino, Eriselda; Geidl, Wolfgang; Naber, Inga; Weißenfels, Anja; Klamroth, Sarah; Gelius, Peter; Abu-Omar, Karim; Pfeifer, Klaus (BMJ Open, 2021)
Introduction In its attempt to establish effective physical activity promotion methods, research on physical activity referral schemes (PARS) is attracting significant attention. Sometimes known as physical activity on prescription schemes, PARS involve a well-defined procedure whereby a primary healthcare professional introduces a participant to the topic of physical activity and employs prescription or referral forms to connect the participant to physical activity opportunities, such as local fitness offers. The planned systematic review will focus on these referral routes and scheme components and how they are integrated into various PARS models worldwide. We seek to identify the evidence-based core components that play the most important roles in the effectiveness of PARS. Methods and analysis The development and reporting of the protocol follow the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocols guidelines. We plan to conduct a systematic main literature search on PubMed, Scopus, Web of Science, CINAHL, HTA, SpringerLink and other databases. We will include studies that report outcomes on physical activity, PARS uptake and adherence rates or descriptive information about PARS models. We intend for all review stages, citation screening, data extraction and risk of bias assessment to be conducted by at least two independent reviewers. As a broad spectrum of study designs, including randomised and non-randomised studies of interventions and mixed methods, will be eligible, we will use three separate tools to assess the risk of bias in individual studies. The data will be primarily synthesised narratively, following Intervention Component Analysis. If the data allow, we will perform a random-effects meta-analysis and meta-regression to investigate the impact of specific PARS components on effect sizes. Ethics and dissemination This systematic review does not require formal ethics approval. The results will be submitted to a peer-reviewed journal and international conferences to reach the scientific community. PROSPERO registration number CRD42021233229.
Keywords: physical activity referral scheme; physical activity prescription; exercise referral scheme

Schlüsselkomponenten von Bewegungsversorgungsketten: Eine systematische Übersichtsarbeit - Mino, Eriselda; Geidl, Wolfgang; Hanson, Coral; Mchale, Sheona; Naber, Inga; Weißenfels, Anja; Klamroth, Sarah; Gelius, Peter; Abu-Omar, Karim; Pfeifer, Klaus (Jahrestagung dvs-Kommission Gesundheit, 2022)
Einleitung In vielen Ländern sind Bewegungsversorgungsketten (BVK) zur Förderung der körperlichen Aktivität (KA) etabliert. BVK beginnen meist bei medizinischem Fachpersonal, welches den Patientinnen und Patienten eigenständige KA oder ein betreutes Bewegungsförderungsprogramm verschreibt. BVK können jedoch auch deutlich komplexer sein und variieren dabei hinsichtlich ihrer Merkmale und Interventionskomponenten. Das Ziel dieser Arbeit ist eine systematische Übersicht der Schlüsselkomponenten von BVK (vgl. Mino et al. 2021). Methode Es wurde eine systematische Suche nach Artikeln in verschiedenen Datenbanken (u.a. Pub-Med, Scopus) durchgeführt (bis April 2022). Eingeschlossen wurden (quasi-)experimentelle, prospektive, qualitative und Mixed-Methods-Studien, die BVK für inaktive Menschen mit vorhandenen nichtübertragbaren Erkrankungen oder assoziierten Risikofaktoren untersuchen. In der Volltextanalyse wurden Programmaufnahme und -adhärenz sowie Änderungen der KA extrahiert; weiterhin wurden mittels Interventionskomponentenanalyse (Sutcliffe et al. 2015) und einer Checkliste (Hanson et al. 2020) Strukturen und Inhalte der BVK analysiert. Ergebnisse Die Suche ergab 4893 Studien von denen 54 eingeschlossen wurden. Daten zur KA wurden von 43 Studien erhoben, 37 Studien berichteten Programmaufnahme oder –adhärenz. Die häufigsten Schlüsselkomponenten der Ketten sind ein patientenzentrierter Ansatz, Individualisierung, Screening, Eingangs- und Ausgangsassessment, motivierende Beratungen, Kurzberatung, Verschreibung oder Überweisung, betreutes oder unbeaufsichtigtes Trainingsprogramm, strukturierte Nachbereitung und Nachsorgestrategien. Diskussion Diese Arbeit bietet einen internationalen Überblick der Schlüsselkomponenten von BVK. Im nächsten Schritt werden die einzelnen Interventionskomponenten bezüglich ihrer Wirksamkeit für Bewegungsförderung, Programmaufnahme und –adhärenz analysiert. Die Ergebnisse liefern wichtige Informationen für die Ausgestaltungsmöglichkeiten von BVK. Literatur Mino E, Geidl W, Naber I, et al. Physical activity referral scheme components: a study protocol for systematic review and meta-regression. BMJ Open 2021;11(e049549). Sutcliffe K, Thomas J, Stokes G, et al. Intervention component analysis (ICA): a pragmatic approach for identifying the critical features of complex interventions. Syst Rev 2015;4:140. Hanson CL, Oliver EJ, Dodd-Reynolds CJ, et al. A modified Delphi study to gain consensus for a taxonomy to report and classify physical activity referral schemes (pars). Int J Behav Nutr Phys Act 2020;17:158.
Keywords: Bewegungsförderung; Versorgung; Bewegungsversorgungskette

Sensomotorisches Laufbandtraining bei Morbus Parkinson - Klamroth, Sarah; Steib, Simon; Pfeifer, Klaus (Zeitschrift für Komplementärmedizin, 2017)
Keywords: Morbus Parkinson; Sensomotorisches Laufbandtraining

Sensomotorisches Laufbandtraining in der Rehabilitation von Gangstörungen bei Patienten mit Morbus Parkinson - Klamroth, Sarah; Gaßner, Heiko; Winkler, Jürgen; Eskofier, Björn; Klucken, Jochen; Pfeifer, Klaus; Steib, Simon (27. Rehabilitationswissenschaftliches Kolloquium: Rehabilitation bewegt!, 2018)

The association of physical activity referral scheme’ components with physical activity level, scheme uptake and adherence rates: a systematic review, meta-analysis with meta-regression - Geidl, Wolfgang; Brandmeier, Anna; Klamroth, Sarah; Naber, Inga; Weißenfels, Anja; Abu-Omar, Karim; Pfeifer, Klaus; Mino, Eriselda; Hanson, Coral L.; Mchale, Sheona; Schuler, Michael; Gelius, Peter; et al. (Proceedings of the 15th conference of HEPA Europe "Optimising health enhancing physical activity: the importance of inclusion", 2024)
Purpose Physical activity referral schemes (PARS) are complex interventions comprised of multiple components such as screening, brief advice, and written prescription. This study aimed to investigate the relationship between PARS components and physical activity, uptake, and adherence rates. Additionally, the overall effect of PARS is analysed. Methods 6 databases were searched for studies published between 1990-2023; included PARS with participants ≥16 years old; and reported either physical activity, uptake or adherence outcomes. GRADE was used to assess quality of evidence. Separate random-effects meta-analysis by comparison group were conducted for physical activity. Uptake and adherence rates were pooled using proportional meta-analysis. The PARS components were analyzed via univariate meta-regression. Results We included 52 studies from which 50 targeted people with, or at risk of, non-communicable diseases. PARS were compared with usual care (11 RCTs, Hedges’ g = 0.18, 95%CI 0.12 to 0.25), physical activity advice (5 RCTs, Hedges’ g=-0.6, 95%CI -0.21 to 0.10), or enhanced PARS (9 RCTs, Hedges’ g = 0.07, 95%CI -0.03 to 0.18). The pooled uptake rate was 87% (95%CI 77% to 94%) among 14 RCTs and 68% (95%CI 51% to 83%) among 14 non-experimental studies. The adherence rate across 16 RCTs and 18 non-experimental studies was 68% (95%CI 55% to 80%) and 53% (95%CI 42% to 63%) respectively. The meta-regression showed that PARS incorporating a person-centered approach, screening, and brief advice had higher adherence rates. In contrast, PARS offering physical activity sessions had lower adherence rates. No other component-outcome relationship reached statistical significance. Conclusion High certainty of evidence confirms a small effect of PARS in increasing physical activity compared to usual care. The evidence comparing PARS with advice and enhance scheme versions is inconclusive and comes from low certainty of evidence. Four out of the 19 PARS components may predict adherence. Practical implications The results improve our understanding of effective PARS components in relation to physical activity promotion, scheme uptake and adherence and thus support the future development of optimal PARS. Funding The study was conducted within the project BewegtVersorgt, which is funded by the Federal Ministry of Health based on a resolution of the German ‘Bundestag’ by the federal government.
Keywords: physical activity referral scheme; physical activity

The effects of exercise therapy on postural instability in Parkinson´s disease: A Meta-analysis. - Klamroth, Sarah; Steib, Simon; Devan, Surendar; Pfeifer, Klaus (Journal of Neurologic Physical Therapy, 2016)
Keywords: balance; exercise; Parkinson disease; postural control

Überprüfung einer entwickelten Versorgungsstruktur zur Bewegungsförderung für Menschen mit nichtübertragbaren Erkrankungen – Protokoll über eine pragmatische Studie im Cluster-Design - Weißenfels, Anja; Mino, Eriselda; Naber, Inga; Klamroth, Sarah; Gelius, Peter; Geidl, Wolfgang; Abu-Omar, Karim; Pfeifer, Klaus (20. Deutscher Kongress für Versorgungsforschung, 2021)

Zur Rolle des Bewegungsfachberufs in internationalen Bewegungsversorgungsstrukturen - ein internationaler Vergleich - Weißenfels, Anja; Naber, Inga; Mino, Eriselda; Klamroth, Sarah; Geidl, Wolfgang; Abu-Omar, Karim; Pfeifer, Klaus (Bewegungstherapie und Gesundheitssport, 2020)
Aufgrund einer zunehmenden körperlichen Inaktivität der Weltbevölkerung haben durch Bewegungsmangel induzierte Erkrankungen in den letzten Jahren stark zugenommen. Nicht nur zur Prävention nichtübertragbarer Erkrankungen (noncommunicable diseases: NCD), sondern auch aus rehabilitativer Perspektive ist regelmäßige körperliche Aktivität ein essenzieller Gesundheitsfaktor und eine Ergänzung oder Alternative zur medikamentösen Behandlung. Ärztlich initiierte Bewegungsversorgung ist in vielen Ländern bereits in den jeweiligen Gesundheitssystemen etabliert, während die deutsche Regelversorgung hier bislang noch Defizite aufweist. Die Bewegungsversorgungsmodelle aus Schweden, Dänemark und Neuseeland zeigen deutliche Stärken bei der interdisziplinären Zusammenarbeit unterschiedlicher Berufsgruppen (Ärzt*innen, Bewegungsfachberufe) sowie der Integration verhaltensbezogener Bewegungsförderung. Personen aus Bewegungsfachberufen (u. a. Physio-, Bewegungs- und Sporttherapeut*innen) haben international eine einflussreiche Rolle bei der individuellen Verhaltensänderung zur Steigerung körperlicher Aktivität, und im Vergleich zum deutschen System ist das Aufgabengebiet dieser Berufsgruppe bedeutsam erweitert. International betrachtet setzen Bewegungsfachberufe regelhaft theoriebezogene Inhalte der Bewegungsförderung ein, wie z. B. motivationale Gesprächsführung (MI) oder auch Follow-up-Telefonanrufe, und sind teilweise sogar befugt, Bewegungsrezepte auszustellen. Der systematische Einsatz von Inhalten zur Bewegungsförderung durch Bewegungsfachberufe und die gezielte interdisziplinäre Zusammenarbeit mit Ärzt*innen werden im hiesigen Gesundheitssystem bislang kaum oder nur rudimentär verfolgt, weshalb das Projekt BewegtVersorgt neben der Etablierung einer wirkungsvollen Bewegungsversorgungskette besonders das Aufgabengebiet der Bewegungsfachberufe in den Fokus nimm
Keywords: Körperliche Aktivität; ärztlich initiierte Bewegungsförderung; Bewegungsversorgungsketten; nichtübertragbare Erkrankungen; Primärversorgung